2014
DOI: 10.1021/ma501817n
|View full text |Cite
|
Sign up to set email alerts
|

N-Heterocyclic Carbene-Based Conducting Polymer–Gold Nanoparticle Hybrids and Their Catalytic Application

Abstract: Hybrid nanocomposites of N-heterocyclic carbene (NHC)-functionalized conducting polymers (CPs) with gold nanoparticles (AuNPs) were prepared by concurrent disproportionation and oxidative coupling. The formation of hybrid nanocomposites, NHC-CP/AuNPs, in the simultaneous process was confirmed by transmission electron microscopy, powder X-ray diffraction, cyclic voltammetry, and 13C solid-state NMR analyses. More importantly, the NHC group played a pivotal role in the dispersion of AuNPs. Further, NHC-CP/AuNPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 38 publications
2
49
0
Order By: Relevance
“…8e,g−j Despite the broad scope of known gold-catalyzed transformations 9 and the growing body of work on NHC-Au surface chemistry, 5,6b,10 catalysis by NHC-ligated Au NPs has been scarcely explored, and to our knowledge, only been applied to hydrogenation chemistry or electrochemical CO 2 reduction. 8k,l, 11 A main challenge has been to systematically vary the ligand structure without perturbing Au NP stability to Au complex leaching and/or NP aggregation. Work in our laboratories on supported dendrimer encapsulated Au NPs 1d−f provided a platform for overcoming this challenge.…”
Section: ■ Introductionmentioning
confidence: 99%
“…8e,g−j Despite the broad scope of known gold-catalyzed transformations 9 and the growing body of work on NHC-Au surface chemistry, 5,6b,10 catalysis by NHC-ligated Au NPs has been scarcely explored, and to our knowledge, only been applied to hydrogenation chemistry or electrochemical CO 2 reduction. 8k,l, 11 A main challenge has been to systematically vary the ligand structure without perturbing Au NP stability to Au complex leaching and/or NP aggregation. Work in our laboratories on supported dendrimer encapsulated Au NPs 1d−f provided a platform for overcoming this challenge.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Even though a lot of examples are known for NHC-transition metal complexes as the building block into the backbone of polymeric materials, the complete study of the coinage metals in the conducting polymer material with a combination of NHC building block still not investigated. 28 With the widespread and increasing interest in NHC materials, there is a growing realization that the presence of metal centers in CPs can result in new and valuable properties. 26 NHCs with Ag and Au containing polymer thin films revealed that highly reversible electrochromic phenomena have been reported by Cowley and coworkers.…”
Section: Introductionmentioning
confidence: 99%
“…Recent Advances in the Schiff Bases and NHCs as Ligands in the Cross-Coupling Reactions Song and co-workers [157] reported hybrid nanocomposites of NHC-functionalized conducting polymers with gold NPs (AuNPs) prepared by concurrent disproportionation and oxidative coupling in 89% yield as shown in Scheme 120. The NHC group played a pivotal role in the dispersion of AuNPs.…”
Section: April 2019mentioning
confidence: 99%